Partisipasi Masyarakat dalam Pengembangan Desa Wisata Timbang Jaya - Saragih, Yoana Romauli; Yanti, Dewi (Tourism, Hospitality And Culture Insights Journal, 2024)
Timbang Jaya Village has the potential for extraordinary tourist attractions including natural tourism, culinary tourism and local cultural tourism supported by attractions, accommodation and other facilities. Therefore, this study aims to analyze community participation in the development of Timbang Jaya Tourism Village. This research uses a qualitative approach by involving the active participation of local communities, village government, and Pokdarwis. The results of this study show that community participation in the development of Timbang Jaya Tourism Village has a positive impact in several aspects. However, this study also identified several obstacles that local communities still face, such as the lack of financial resources channeled to the community, and the fragmentation of land from each individual or company. Based on these findings, it is recommended that the government move quickly in channeling funds to the community and assisting in the problems faced by the community, as well as strengthening cooperation between various related parties to achieve more effective goals.